Pengaruh Media Sosial dan Harga Terhadap Loyalitas Konsumen Pada Woodcraft “tanganketiga” - Winda Oktaviani (Universitas Kuningan, 2020)
AbstractThe object of this research is a creative inustry in manufacturing. This study aims to determine the response of consumers regarding social media, pricing and customer loyalty